Efficacy and safety of Chinese herbal medicines combined with biomedicine in the treatment of idiopathic membranous nephropathy: a systematic review and network meta-analysis - Zhu, He; Xiao, Yunming; Ji, Yue (Frontiers in Pharmacology, 2024)
Background: Chinese herbal medicines have been extensively used to treat idiopathic membranous nephropathy (IMN). However, their efficacy and safety remain uncertain. Therefore, this study employed a network meta-analysis to evaluate the efficacy and safety of various Chinese herbal medicines in combination with biomedicines for treating IMN.: A comprehensive literature search was performed across several databases, including PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), WanFang Data, VIP Database, and Chinese Biomedical Literature Database (CBM), to identify randomized controlled trials (RCTs) concerning the treatment of IMN using a combination of Chinese herbal medicines and biomedicine, up to May 31, 2024. Two researchers independently conducted the literature screening and data extraction. The quality of the included studies was assessed using the Cochrane quality review manual, and Stata 14.2 software was employed for network meta-analysis. Results: A total of 31 RCTs involving 2195 IMN patients and 15 different Chinese herbal medicines were analyzed. The network meta-analysis revealed that QQC+BM (84.7%) was the most effective in reducing 24-hour urinary protein. For improving serum albumin, HZC+BM (86%) was the most effective.LGT+BM (77.2%) was the best for enhancing serum creatinine levels. MXC+BM demonstrated the highest effectiveness in lowering total cholesterol (89%) and triglycerides (97%). Lastly, WZC+BM (90.8%) was the most effective in reducing the incidence of adverse reactions.The current evidence suggests that integrating Chinese herbal medicines with biomedicine may provide significant benefits in treating IMN. Specifically, QQC+BM appears to be the most effective in reducing 24-hour urinary protein, HZC+BM seems to excel in improving serum albumin levels, MXC+BM is noted for its effectiveness in lowering triglycerides and total cholesterol, LGT+BM is optimal for reducing serum creatinine, and WZC+BM shows the lowest rate of adverse reactions. Nevertheless, due to limitations in the quantity and quality of the included studies, further validation of these conclusions is necessary.